نمذجة معامل الشكل لماكي السنديان العاديQuercus calliprinos Webb. النامي على السفوح الشرقية للجبال الساحلية - سورية - علي, وائل; المحمود, فادي (Latakia University Journal -Biological Sciences Series, 2016)
تهدف هذه الدراسة إلى تصميم موديل (نموذج) رياضي لحساب معامل الشكل للأخلاف السنديان العادي الموجود على السفوح الشرقية للجبال الساحلية، مما يساعد الحراجيين في تقدير حجم الأشجار والمجموعات الحرجية بشكل أكثر دقةً.تم خلال العام 2014 قطع 129 خلفة من أخلاف السنديان العادي تتنوع في أعمارها وقياساتها وتقع في مجموعات حرجية طبيعية موزعة على كامل السفح الشرقي للجبال الساحلية متنوعة في كثافتها وخصوبة مواقعها. تم قياس أقطار الأخلاف المقطوعة على ارتفاعات مختلفة، كما تم حساب حجومها وحجوم الأسطوانات المكافئة لها ومن ثم الحصول على قيم معامل الشكل. تم استخدام 70% (90 خلفة) من البيانات الناتجة لتصميم موديل معامل الشكل و 30% (39 خلفة) منها لإجراء عدد من الاختبارات الإحصائية للموديلات الناتجة. تم الحصول على عدد من الموديلات الرياضية لحساب معامل الشكل باستخدام معادلات الانحدار غير الخطي Nonlinear Regression في البرنامج الإحصائي SPSS حيث تم اختيار أفضلها. بلغت قيمة معامل التحديد المعدل لأفضل الموديلات (0.77R²adj = ). كما بلغت قيمة المتوسط النسبي لخطأ الموديل أثناء اختبارات الجودة للموديل الأفضل(3.6%- = ) و قيمة دقة الموديل (15% = ). للحصول على قيمة خطأ أقل ودقة أعلى للموديل ينصح باستخدام قاعدة بيانات أوسع لتشمل جميع مناطق انتشار ماكي السنديان العادي في سورية.This study aims to construct a mathematical model to calculate the form factor of Palestine Oak Maquis grown on the eastern versants of coastal mountains. The form factor model can help foresters to precisely estimate the volume of tree and forest stands.In the year 2014, 129 oak shoots of various ages and sizes, located in natural stands of different densities and site qualities covering all conditions of region grown on, were felled.Diameters at different heights of the felled shoots were measured; shoots volumes and volumes of equivalent cylinders were calculated, and consequently the values of shoot form factor were computed. The dataset was randomly split into two parts, 70% (90 shoots) of the data for constructing form factor model and 30% (39 trees) for model validation. Several form factor models were developed using the non-linear regression equations in the statistical program SPSS. Best fit to the data was selected and value of the coefficient of determination adjusted (R²adj) was about 0.77. The model has been validated using several statistical methods, the relative bias of the best model ( ) was ca. -3.6 %, while the value of model accuracy ) ) was 15%. In order to obtain lower value of model relative bias and higher value of accuracy, it’s recommended to use a larger database comprising all distribution areas of oak Maquis in Syria.